Echocardiography protocol for early detection of cardiac dysfunction in childhood cancer survivors in the multicenter DCCSS LATER 2 CARD study: Design, feasibility, and reproducibility. - Merkx, Remy; Leerink, Jan M.; Feijen, Elisabeth (Lieke) A.M.; Kremer, Leontien C.M.; de Baat, Esmée C.; Bellersen, Louise; van Dalen, Elvira C.; van Dulmen‐den Broeder, Eline; van der Heiden‐van der Loo, Margriet; van den Heuvel‐Eibrink, Marry M.; Korte, Chris L. de; Loonen, Jacqueline; et al. (Echocardiography, 2021)
Background: Cardiotoxicity is a well‐known side effect after anthracyclines and chest radiotherapy in childhood cancer survivors (CCS). The DCCSS LATER 2 CARD (cardiology) study includes evaluation of echocardiographic measurements for early identification of CCS at highest risk of developing heart failure. This paper describes the design, feasibility, and reproducibility of the echocardiography protocol. Methods: Echocardiograms from CCS and sibling controls were prospectively obtained at the participating centers and centrally analyzed. We describe the image acquisition, measurement protocol, and software‐specific considerations for myocardial strain analyses. We report the feasibility of the primary outcomes of systolic and diastolic function, as well as reproducibility analyses in 30 subjects. Results: We obtained 1,679 echocardiograms. Biplane ejection fraction (LVEF) measurement was feasible in 91% and 96% of CCS and siblings, respectively, global longitudinal strain (GLS) in 80% and 91%, global circumferential strain (GCS) in 86% and 89%, and ≥2 diastolic function parameters in 99% and 100%, right ventricle free wall strain (RVFWS) in 57% and 65%, and left atrial reservoir strain (LASr) in 72% and 79%. Intra‐class correlation coefficients for inter‐observer variability were 0.85 for LVEF, 0.76 for GLS, 0.70 for GCS, 0.89 for RVFWS and 0.89 for LASr. Intra‐class correlation coefficients for intra‐observer variability were 0.87 for LVEF, 0.82 for GLS, 0.82 for GCS, 0.85 for RVFWS and 0.79 for LASr. Conclusion: The DCCSS LATER 2 CARD study includes a protocolized echocardiogram, with feasible and reproducible primary outcome measurements. This ensures high‐quality outcome data for prevalence estimates and for reliable comparison of cardiac function parameters.